2023
DOI: 10.3390/ijerph20032146
|View full text |Cite
|
Sign up to set email alerts
|

Links between COVID-19 and Alzheimer’s Disease—What Do We Already Know?

Abstract: Alzheimer’s disease (AD) is a life-changing condition whose etiology is explained by several hypotheses. Recently, a new virus contributed to the evidence of viral involvement in AD: the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes the COVID-19 coronavirus disease. AD was found to be one of the most common COVID-19 comorbidities, and it was found to increase mortality from this disease as well. Moreover, AD patients were observed to present with the distinct clinical features of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…The most commonly applied technique is a T 1-weighted dynamic contrast-enhanced (DCE)-MRI, during which a gadolinium-based contrast agent is injected intravenously; leakage of the contrast agent can be detected when it crosses the damaged BBB (e.g., 70 , 71 ). It should be noted that there is substantial comorbidity between COVID-19 and AD ( 72 , 73 ) and the chronic neurological sequelae in Long COVID are also present in AD clinical phenomenology. Furthermore, there is evidence indicating APOE e4e4 genotype as a potential genetic determinant for the development of severe COVID-19 ( 74 ), and ApoE e4e4 homozygotes are more likely to be COVID-19 test positive ( 75 ).…”
Section: Relevant Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly applied technique is a T 1-weighted dynamic contrast-enhanced (DCE)-MRI, during which a gadolinium-based contrast agent is injected intravenously; leakage of the contrast agent can be detected when it crosses the damaged BBB (e.g., 70 , 71 ). It should be noted that there is substantial comorbidity between COVID-19 and AD ( 72 , 73 ) and the chronic neurological sequelae in Long COVID are also present in AD clinical phenomenology. Furthermore, there is evidence indicating APOE e4e4 genotype as a potential genetic determinant for the development of severe COVID-19 ( 74 ), and ApoE e4e4 homozygotes are more likely to be COVID-19 test positive ( 75 ).…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…Furthermore, there is evidence indicating APOE e4e4 genotype as a potential genetic determinant for the development of severe COVID-19 ( 74 ), and ApoE e4e4 homozygotes are more likely to be COVID-19 test positive ( 75 ). Furthermore, ApoE e4e4 homozygotes were found to be at the highest risk of sporadic AD ( 73 , 76 ). However, the mechanism underlying this association remains unclear ( 74 ).…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…Social connectivity/family bonding, as a means of overcoming loneliness, is one of the most important social measures that can delay the progression of dementia in patients with Alzheimer’s disease [ 87 , 88 ] and thereby social connectedness and healthy relationships are protective factors for patients with Alzheimer’s disease [ 89–91 ]. The Harvard adult study, the longest longitudinal study on human life that followed 268 Harvard sophomores for a period of 80 years to understand what the key factors that lead to a longer and healthier life, reported that one of the most powerful indicators of good health and happiness is strong, trustworthy and satisfied relationships.…”
Section: Perspectivesmentioning
confidence: 99%
“…Despite the aforementioned variations in design and demographics observed in COVID cognition studies, however, there is a growing body of evidence indicating that individuals who have recovered from COVID-19 may be susceptible to the development of mild cognitive impairment and degenerative dementia. [10][11][12] Additionally, there is strong evidence suggesting the presence of certain neuropsychiatric symptoms such as depression and anxiety after COVID-19 infection. 2,13,14 Here, it is noteworthy to remember that the presence of comorbid preexisting conditions, along with strict pandemic restrictions that have significant neuropsychiatric consequences, can mutually reinforce one another in a vicious cycle, ultimately impairing cognition and consequently elevating one's risk to degenerative dementia.…”
Section: Introductionmentioning
confidence: 99%
“…However, as mentioned above, these studies failed to shed light on how specific cognitive regions relate to the cognitive functions. Despite the aforementioned variations in design and demographics observed in COVID cognition studies, however, there is a growing body of evidence indicating that individuals who have recovered from COVID‐19 may be susceptible to the development of mild cognitive impairment and degenerative dementia 10–12 . Additionally, there is strong evidence suggesting the presence of certain neuropsychiatric symptoms such as depression and anxiety after COVID‐19 infection 2,13,14 .…”
Section: Introductionmentioning
confidence: 99%